Response of serum lipids to a fat meal in Black South African subjects with different apoe genotypes - Dikotope, Sekgothe Abram (University of Limpopo (Turfloop Campus), 2013)
Objectives The present study investigated how the serum lipids responded to a high-fat meal in black South African subjects with different APOE genotypes, a population that until recently was reported to be consuming a traditional diet of low fat and high carbohydrates. Methods Sixty students (males and females) of the University of Limpopo, Turfloop Campus were successfully genotyped using Restriction Fragment Length Polymorphism (RFLP) and grouped into four APOE genotype groups; ε2, ε2/ε4, ε3 and ε4. Only thirty-three subjects volunteered to participate in the oral fat-tolerance test (OFTT), but two were excluded for having abnormal total cholesterol (6.05 mmol/l) and LDL cholesterol (3.12 mmol/l) so only 31 subjects were left. The numbers per group were ε2=5, ε2/ε4=8, ε3=9 and ε4=9. After an overnight fast blood was drawn for measurements of baseline serum parameters. Subjects were administered a high fat meal 30 minutes after the baseline blood sample was drawn. Blood was drawn at intervals of 20, 40, 60, 120, 180, 240, 300 and 360 minutes for measurements of postprandial serum parameter levels. Serum parameters measured were triglyceride, total cholesterol, low density lipoprotein cholesterol, high density lipoprotein cholesterol, glucose and insulin. Results Mean levels of serum lipids at baseline in mmol/l were as follows; group 1[TG=0.69(0.55-0.81), TCHOL=3.10±0.29, HDL-C=1.12±0.32, LDLC= 1.67±0.28]; group 2 [TG=0.61(0.53-1.00), TCHOL=2.98±0.53, HDLC= 1.20±0.37, LDL-C=1.43±0.37]; group 3 [TG=0.67(0.28-0.86), TCHOL=2.96±0.54, HDL-C=1.22±0.30, LDL-C=1.46±0.47]; group 4 [TG=0.76(0.51-1.16), TCHOL=3.27±0.51, HDL-C=1.12±0.17, LDLC= 1.79±0.47]. There was no significant difference in the mean levels of baseline triglyceride, total cholesterol, low density lipoprotein cholesterol, and ix high density lipoprotein cholesterol between the APOE groups hence no significant difference in the response to a fatty meal. Conclusions There was no significant change in serum lipid concentrations after a fatty meal in individuals with different APOE genotypes in a population that consume a traditional diet of low fat and high carbohydrates. Due to the small sample size, the results should be interpreted with caution. A larger study is recommended to ascertain the role of APOE genotypes on serum lipid response to a fatty meal in Black South African population.
Thesis (M.Sc. (Chemical Pathology)) --University of Limpopo, 2013
Keywords: Serum lipids; High fat meal; Apoe genotype; 613.2; Blood cholesterol; Blood proteins